Making sense of corruption - Rothstein, Bo (Cambridge University Press, 2017)
Corruption and the relevance of political science -- Mapping related disciplines -- The evolution of corruption as a concept -- Corruption and human rights -- Corruption and clientelism -- Corruption and patronage -- Corruption and patrimonialism -- Corruption, state capture and political particularism -- The Chinese exception and alternative -- In conclusion: what is the opposite of corruption?